2013
DOI: 10.1007/s10059-013-0071-4
|View full text |Cite
|
Sign up to set email alerts
|

Co-Expression of Monodehydroascorbate Reductase and Dehydroascorbate Reductase from Brassica rapa Effectively Confers Tolerance to Freezing-Induced Oxidative Stress

Abstract: Plants are exposed to various environmental stresses and have therefore developed antioxidant enzymes and molecules to protect their cellular components against toxicity derived from reactive oxygen species (ROS). Ascorbate is a very important antioxidant molecule in plants, and monodehydroascorbate reductase (MDHAR; EC 1.6.5.4) and dehydroascorbate reductase (DHAR; EC 1.8.5.1) are essential to regeneration of ascorbate for maintenance of ROS scavenging ability. The MDHAR and DHAR genes from Brassica rapa were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 62 publications
3
17
0
Order By: Relevance
“…Under salt stress, transgenic plum plantlet with SOD expressed non-enzymatic antioxidants, glutathione and ascorbate which lowered hydrogen peroxide level (Diaz-Vivancos et al 2013). In our study, it is likely that upregulation of SOD and a peroxidase is involved in scavenging ROS.Another protein, monodehydroascorbate reductase (MDHAR) which was upregulated only in B group is essential for regenerating ascorbate during ROS scavenging activity as evidenced by transgenic Brassica rapa overexpressing MDHAR and dehydroascorbate reductase (DHAR) increased glutathione and phenolics thereby alleviating redox stress leading to cold tolerance(Shin et al 2013).…”
mentioning
confidence: 75%
“…Under salt stress, transgenic plum plantlet with SOD expressed non-enzymatic antioxidants, glutathione and ascorbate which lowered hydrogen peroxide level (Diaz-Vivancos et al 2013). In our study, it is likely that upregulation of SOD and a peroxidase is involved in scavenging ROS.Another protein, monodehydroascorbate reductase (MDHAR) which was upregulated only in B group is essential for regenerating ascorbate during ROS scavenging activity as evidenced by transgenic Brassica rapa overexpressing MDHAR and dehydroascorbate reductase (DHAR) increased glutathione and phenolics thereby alleviating redox stress leading to cold tolerance(Shin et al 2013).…”
mentioning
confidence: 75%
“…Previous studies have shown that multiple ion channel pores in cell participate to stress responses in cyanobacterial cells (Los and Murata, 2004;Kim et al, 2018). SDS and cold stress were a surfactant that damage lipid membranes, thereby disrupting cellular redox homeostasis and leading to apoptosis (Kwon et al, 2003;Tahara et al, 2012;Shin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…MDAR is an enzyme that catalyzes the conversion of monodehydroascorbate in ascorbate [NADH + H + + 2 monodehydroascorbate → NAD + + 2 ascorbate]. MDHAR activation in response to various stress conditions has been observed in many plant species (Shin et al, 2013). Ascorbate is a very important antioxidant molecule in plants for the maintenance of ROS scavenging ability.…”
Section: Discussionmentioning
confidence: 99%